2023
DOI: 10.3390/ani13203238
|View full text |Cite
|
Sign up to set email alerts
|

The Chemical Characteristics and In Vitro Degradability of Pineapple By-Products as Potential Feed for Ruminants

Dieu donné Kiatti,
Alessandro Vastolo,
Bossima Ivan Koura
et al.

Abstract: Pineapple fruit, which is cultivated in tropical and subtropical areas, is processed by the food industry, generating a large amount of waste. Using pineapple by-products in animal nutrition could reduce feeding costs and contribute to the containment of pollution. The chemical composition and the in vitro fermentation of five pineapple by-products (crown, bud end, peel, core, and pomace) from two West African pineapple varieties (Smooth Cayenne—SC and Sugarloaf—SL) were evaluated. Significant differences were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…The study found that combining cassava peels with Cajanus cajan hay in a 1:3 ratio resulted in an improvement in nitrogen content, digestibility, and optimal levels. According to Kiatti et al (49), fruit by-products can be used as a base for ruminant feed based on their nutritional content of sugar and fiber. Pineapple by-products, specifically the core and pomace, were found to have low structural carbohydrate content, high in vitro degradability, and high volatile fatty acid production.…”
Section: Effect Of Using Alternative Feeds On Dry Matter Intake and D...mentioning
confidence: 99%
“…The study found that combining cassava peels with Cajanus cajan hay in a 1:3 ratio resulted in an improvement in nitrogen content, digestibility, and optimal levels. According to Kiatti et al (49), fruit by-products can be used as a base for ruminant feed based on their nutritional content of sugar and fiber. Pineapple by-products, specifically the core and pomace, were found to have low structural carbohydrate content, high in vitro degradability, and high volatile fatty acid production.…”
Section: Effect Of Using Alternative Feeds On Dry Matter Intake and D...mentioning
confidence: 99%